Pengaruh Disiplin Kerja Terhadap Kualitas Pelayanan Aparat Pada Kantor Desa Tonralipue Kecamatan Tanasitolo Kabupaten Wajo - Maspawati Maspawati; Amrizal Akmul; Supriadi Mujibu (Journal of Research and Development on Public Policy, 2024)
This study aims to determine; (1) work discipline of officers at the Tonralipue Village Office, Tanasitolo District, Wajo Regency; (2) Quality of service at the Tonlipue Village Office, Tanasitolo District, Wajo Regency; (3) The influence of work discipline on the quality of service for officers at the Tonralipue Village Office, Tanasitolo District, Wajo Regency. For this reason, information and information were collected by making direct observations [observations]. The subjects in this research were people who had interests at the Tonralipue Village Office and a sample of 26 people was taken, and looked for supporting data in the form of official documents. Research data is processed by calculating the percentage value of answers given by respondents in research questionnaires, both questionnaires regarding work discipline and service quality. And to determine the influence of work discipline on the quality of employee service, both separately and together, the correlation and linear regression values ​​of the research variables were calculated. The results of the research show that the discipline applied by the village head is work discipline that has been implemented with very good quality. This shows that the results of infreential statistical management reveal that work discipline has a positive effect on the quality of service by officers. On the basis of the results of this research, it is recommended that the Village and Officials at the Tonralipue Village Office, Tanasitolo District, Wajo Regency, try to maintain the quality of work discipline and service quality of the officers that has been successfully realized at this time, and even try to improve it further in the future because it has been proven to have a positive impact on apparatus work discipline.